AKIBAT HUKUM DAN DAMPAK PSIKOLOGIS PERKAWINAN SIRI BAGI PEREMPUAN DAN ANAK-ANAKNYA: Kajian Teoretis Menurut Undang-Undang dan KHI - Rudy Catur Rohman; Muhammad Maddarik (MAQASHID Jurnal Hukum Islam, 2020)
Marriage is the gate of life that is usually passed by mankind in carrying out life as husband and wife. That Allah SWT. create something with pairs, male and female, male and female animals, day and night, and so on. The practice of siri marriage is still a lot to this day. In fact, unregistered marriage has a very detrimental impact on women and their children. A siri marriage or what is known by various other terms such as 'married under the hands', 'kawin siri' or 'nikah siri', is a marriage that is carried out based on religious rules or customs and is not registered at the office of a marriage registrar (KUA for those who are Muslims, Civil Registry Office for non-Muslims). Even though it is legal according to religion, marriage under the hand has no legal protection. So that it has legal consequences both legally and positively in Indonesia and has a psychological impact on several parties, especially women / wives and their children.